EFFECT OF BOKASHI BOTTOM ASH DOSAGES ON THE GROWTH OF VETIVER GRASS (Vetiveria zizanioides) AND ITS LEAD CONTENT - NUNUNG SONDARI (Puslitbang tekMIRA, 2011)
The experiment was conducted at a greenhouse of Agricultural Faculty of Winaya Mukti University Tanjungsari Sumedang, West Java, from May to October 2009. The objective of this research was to see the effect of the bokashi bottom ash application on the growth and of vertiver grass and its lead content. The experiment used the environmental design of Randomized Block Design (RBD) that consist of five treatments and is repeated five times. The factor was the bokashi bottom ash dosages ( 0,5,10, 15, and 20 t ha-1 ). The results show that the application of bokashi bottom ash affected the growth of vetiver grass, except shoot root ratio. The dosage of 15 t ha-1 presented a good effect to the plant height, the number of leaves and tillers. The bokashi bottom ash with dosage of 20 t ha-1 wasthe best effect in absorbing lead applied to vetiver grass.